2020
DOI: 10.3390/ma13184117
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Analysis of a Reinforced Wood Lap Joint

Abstract: During the restoration of ancient wood structures, the original material of the structures should be kept as much as possible, so a spliced method by using lap joints is commonly used to repair ancient wood structures. This study studies the mechanical behavior of a lap joint which was reinforced with fiber composite materials or steels. An experimental and numerical analysis were performed to study the strength, stiffness and failure modes of the lap joints. The test results showed that the strengthening effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…They concluded that load-bearing capacity increases with increasing the number of the FRP layers. Ye et al [ 17 ] presented experimental results of the spliced beams with lap joints reinforced with fiber composite materials or steel, indicating better effects of the CFRP sheet reinforcement than that of the CFRP and steel bars due to the better bonding conditions. Similar to the results presented in [ 16 ], the strengthening effectiveness increased with the increase in the reinforcement ratio.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that load-bearing capacity increases with increasing the number of the FRP layers. Ye et al [ 17 ] presented experimental results of the spliced beams with lap joints reinforced with fiber composite materials or steel, indicating better effects of the CFRP sheet reinforcement than that of the CFRP and steel bars due to the better bonding conditions. Similar to the results presented in [ 16 ], the strengthening effectiveness increased with the increase in the reinforcement ratio.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, reinforcement against bending and shear may be required. The strength and stiffness of strengthened element may be enhanced by increasing reinforcement ratio [38]. The application of CFRP laminates to strengthen full-size bent LVL beams, glued into pre-drilled Since bent wooden beams normally fail due to brittle fracture in the tensile zone, placing the reinforcement on the tensile surfaces is an effective way to increase the flexural capacity.…”
Section: Introductionmentioning
confidence: 99%
“…In such cases, reinforcement against bending and shear may be required. The strength and stiffness of strengthened element may be enhanced by increasing reinforcement ratio [38]. The application of CFRP laminates to strengthen full-size bent LVL beams, glued into pre-drilled grooves along the bottom surface and applied to the underside of the beams, is described in [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…Carbon fiber reinforced polymer (CFRP) laminate single-lap joints (SLJs) structure has become the core part of automobile and aircraft structure because of its small number of components, lightweight design, and high connection efficiency [ 1 , 2 , 3 , 4 ]. In the process of fabrication, use, and maintenance, CFRP laminate SLJs adhesively bonded structure are inevitably subjected to low-velocity impact (LVI), resulting in various damages, including matrix damage, fiber damage, and delamination damage, known as barely visible impact damage (BVID) [ 5 , 6 , 7 ], which severely affects the integrity, residual strength, and service life of SLJs.…”
Section: Introductionmentioning
confidence: 99%